2019
DOI: 10.1002/jwmg.21744
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with black bear density and implications for management

Abstract: Wildlife density estimates are important to accurately formulate population management objectives and understand the relationship between habitat characteristics and a species’ abundance. Despite advances in density and abundance estimation methods, management of common game species continues to be challenged by a lack of reliable population estimates. In Washington, USA, statewide American black bear (Ursus americanus) abundance estimates are predicated on density estimates derived from research in the 1970s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 86 publications
2
20
2
Order By: Relevance
“…The existence of used locations amongst the sample of available points (i.e., contamination) has been cited as a cause for bias in model coefficient estimates (Keating and Cherry 2004). Johnson et al (2006), however, reported that contamination rates must be extreme to affect coefficient estimates, and the density of black bears in Southeast Alaska and adjacent regions (0.13–1.51/km 2 ; Peacock et al 2011, Welfelt et al 2019) suggest low levels of contamination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of used locations amongst the sample of available points (i.e., contamination) has been cited as a cause for bias in model coefficient estimates (Keating and Cherry 2004). Johnson et al (2006), however, reported that contamination rates must be extreme to affect coefficient estimates, and the density of black bears in Southeast Alaska and adjacent regions (0.13–1.51/km 2 ; Peacock et al 2011, Welfelt et al 2019) suggest low levels of contamination.…”
Section: Methodsmentioning
confidence: 99%
“…The existence of used locations amongst the sample of available points (i.e., contamination) has been cited as a cause for bias in model coefficient estimates (Keating and Cherry 2004). Johnson et al (2006), however, reported that contamination rates must be extreme to affect coefficient estimates, and the density of black bears in Southeast Alaska and adjacent regions (0.13-1.51/km 2 ; Peacock et al 2011, Welfelt et al 2019) suggest low levels of contamination. We developed a pool of candidate models for each of the first 4 black bear den selection models and included in each candidate model a target covariate of interest (Table 1) we were interested in relating to the relative probability of den presence.…”
Section: Methodsmentioning
confidence: 99%
“…For example, genetic analysis is not suitable to provide information on body weight [71], age [83], or behaviour [84]. Therefore, for some research goals, it would be most optimal to use a different approach, or a combination of noninvasive genetic sampling and another method, preferably also noninvasive [10,[84][85][86].…”
Section: Noninvasive Genetic Assessment Vs Other Research Approachesmentioning
confidence: 99%
“…SCR can estimate the effect of certain habitat types on density and encounter probability, even if individuals are not directly encountered in that habitat, by predicting the locations of individual home range centers in the vicinity of the sample units. One main application of SCR has been research on large carnivores (Proffitt et al 2015, Sun et al 2017, Stetz et al 2019, Welfelt et al 2019), but non-invasive DNA sampling with SCR has also been used to study the relationship of mule deer (Odocoileus hemionus) population density and habitat structure (Brazeal et al 2017).…”
Section: Introductionmentioning
confidence: 99%